Splenic Injuries in Abdominal Trauma Modern Management based on Anatomical Knowledge (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: trauma; gastrospleenic; spleenectomy; spleenorapgy; transplant; OPSI